2017
DOI: 10.1186/s11671-017-2156-z
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Morphological Evolution and Etching Kinetics of Porous Silicon Nanowires During Metal-Assisted Chemical Etching

Abstract: Many potential applications of porous silicon nanowires (SiNWs) fabricated with metal-assisted chemical etching are highly dependent on the precise control of morphology for device optimization. However, the effects of key etching parameters, such as the amount of deposited metal catalyst, HF–oxidant molar ratio (χ), and solvent concentration, on the morphology and etching kinetics of the SiNWs still have not been fully explored. Here, the changes in the nanostructure and etch rate of degenerately doped p-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…The morphological investigation of samples S1-S5 fabricated by the MACE technique revealed that both the length and the research papers diameter of the nanowires increase with increasing etching time. This is consistent with the results of other investigators (Huang et al, 2011;Razek et al, 2014;Vinzons et al, 2017;Bagal et al, 2018) [Figs. 1(a) and 1(b)].…”
Section: Resultssupporting
confidence: 94%
“…The morphological investigation of samples S1-S5 fabricated by the MACE technique revealed that both the length and the research papers diameter of the nanowires increase with increasing etching time. This is consistent with the results of other investigators (Huang et al, 2011;Razek et al, 2014;Vinzons et al, 2017;Bagal et al, 2018) [Figs. 1(a) and 1(b)].…”
Section: Resultssupporting
confidence: 94%
“…Figure 4b gives an etching rate close to 0.152 µm/min. This linear relation has been investigated in literature but with different etching rate values [2,18,33]. The possible reasons behind this increase of SiNWs length with etching time was ascribed to the fact that etching was given more time to proceed and the solution had enough oxidizing species to oxidize and dissolve the formed SiO2.…”
Section: Etching Time Effect On Morphology Of Sinw Arraysmentioning
confidence: 87%
“…Our findings demonstrate that shorter SiNWs are much more optically and electrically active which is auspicious for the use in optoelectronic devices and solar cells applications.Nanomaterials 2020, 10, 404 2 of 18 time-consuming and therefore hindered their applications for commercialized products. In contrast, an effective and promising synthetic method namely metal assisted chemical etching (MACE) has been proposed [2,4,[18][19][20]. This technique is simple, rapid, low cost, and suitable for both industrial and laboratory scales.…”
mentioning
confidence: 99%
“…This synthesis technique was made use of to test a Si nanowire solar cell which reported a low efficiency of 0.5% [328]. The most common type of wet etching-metal assisted chemical (MAC) etching involves a noble metal nanoparticle covering the Si wafer followed by reaction with an etchant [329][330][331]. The etchant facilitates oxidation of the Si wafer beneath the metal and as the process progresses, the Si beneath the metal nanoparticle is etched away forming Si nanowires [282].…”
Section: Fabrication Techniquesmentioning
confidence: 99%